Relationship between cumulative probabilities of equivalent amplitudes and maximums of load factors during the flight in turbulent atmosphere - P. A. Fomichev; N. A. Lavro; S. V. Vakulenko (Научный вестник МГТУ ГА)
The functional relationship between cumulative probability of maximum load factors and cumulative probability of equivalent load factor amplitudes was determined. This relationship was derived from statistical correlation between cycle ratio and amplitude of load factor suggested on the basis of processing of firefighting flight records of load factor. The cumulative probability of maximum load factors and ground-air-ground cycle maximum load factor calculated through the cumulative probability of equivalent load factor amplitudes obtained using the range-pair cycle counting method have good agreement with the results calculated using the peak counting method.